PENGARUH LEVERAGE, KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2013-2015) - Zahirah, Azizah; Nurazlina, Nurazlina; Rusli, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The aim of this study are examine the effect of leverage, institutional ownership, managerial ownership and company size to tax avoidance. Cash effective tax rates (CETR) is used to measure tax avoidance. This study uses secondary data with a sample of 62 companies listed on the Stock Exchange during the period 2013-2015. Determination of the sample was made by applying purposive sampling method. This study used multiple linear regression analysis to examine the influence of independent varibles on the dependent variable. The results of this study showed that the variable of leverage and institutional ownership have effect toward tax avoidance. Meanwhile, managerial ownership and size company have no effect toward tax avoidance. The effect of independent variables on the dependent variable can only explain by 19,3%.Keywords :Leverage, Institutional Ownership, Managerial Ownership, Company Size, Tax Avoidance.